Довженкова енциклопедія: історія, проблеми, перспективи “умовного архіву Олександра Довженка” - Безручко, О. (Студії мистецтвознавчі, 2007)
This article looks on the specifics creation of the Dovzhenko’s Encyclopàedia by the Department of the Cinema and TV Studies of National Ukrainian Academy of Science. For the first time the whole list of Russian and Ukrainian Archives which consist Dovzhneko’s documents are kept. The questions of the history and today’s collaboration between Ukrainian and Russian sides of the commission on Dovzhenko’s archives are given.